Management of Carotid Cavernous Fistula: a Case Report of Carotid Cavernous Fistula (CCF): Poster Presentation - Case Report - Resident - ALAZI; Devi Azri Wahyuni (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Carotid-cavernous fistula (CCF) is an abnormal connection between the carotid arterial system and the sinus cavernous. Abnormal vascular shunt allowed blood to flow either direct or indirect from the carotid artery into the sinus cavernous. The indications for treatment of CCF are increased ocular pressure, double vision, bruits, severe headache, and severe proptosis resulting in keratopathy due to exposed cornea. Management of CCF include conservative management, endovascular intervention, surgery, and radiology intervention. Case Illustration : A 61 years old female came to the hospital complained redness on both eyes since 6 months ago, the redness in these eyes unrelieved even they had been treated. The patient have history given three types of drugs but there was not improvement. physical examination shown proptosis, injection of episcleral, cloudy lens with LOCSS NC2NO2C1P1 on both eyes, other examination also shown bruit on both eyes, Laboratory results was in normal limit. Funduscopic examination shown tigroid appearance. Discussion : Arterialization of the conjunctival vessels is a characteristic feature of CCF, other than physical examination, patient was planned for CT angiography examination to find external causes of injury assessing ICH and ischemia. Patient got external manual compression of the ipsilateral cervical carotid artery for about 30 to 40 seconds four times per hour several times daily for 4-6 weeks. Conclusion : Although CCF initially can be mistaken for conjunctivitis or episcleritis. Methods of therapy for CCF include conservative management, endovascular intervention, surgery, and interventional radiology. CCF itself is generally not life threatening but requires treatment to prevent worsening of the eye